2020
DOI: 10.3389/fpsyg.2020.00892
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Teachers’ Social-Emotional Competence: Development and Validation of a Situational Judgment Test

Abstract: Teachers' social-emotional competence is considered important in order to master the social and emotional challenges inherent in their profession and to build positive teacherstudent relationships. In turn, this is key to both teachers' occupational well-being and positive student development. Nonetheless, an instrument assessing the professionspecific knowledge and skills that teachers need to master the social and emotional demands in the classroom is still lacking. Therefore, we developed the Test of Regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 108 publications
1
33
0
5
Order By: Relevance
“…Finally, researchers should assess specific teaching-related job characteristics and their relationship with work engagement and teachers' well-being (Taris et al, 2017;Salmela-Aro et al, 2019). In this regard, future studies should profitably use profession-specific measures through which teachers' knowledge and skills regarding EI key dimensions can be assessed (e.g., situational judgment tests such as the Test of Regulation in and Understanding of Social Situations in Teaching; Aldrup et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, researchers should assess specific teaching-related job characteristics and their relationship with work engagement and teachers' well-being (Taris et al, 2017;Salmela-Aro et al, 2019). In this regard, future studies should profitably use profession-specific measures through which teachers' knowledge and skills regarding EI key dimensions can be assessed (e.g., situational judgment tests such as the Test of Regulation in and Understanding of Social Situations in Teaching; Aldrup et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the values were found to be in the interval proposed by the authors [43], future studies are expected to test the examined relationships including complementary measures to test emotion regulation abilities in relation to teaching-specific situations. For instance, using situational judgment tests adapted to the challenges preservice teachers may face in their professional development may beneficially contribute to evidence linking the implementation of these abilities with lower exhaustion and greater satisfaction [52]. Moreover, research is needed to test the underlying mechanisms through which self-focused emotion regulation leads to higher study vigor and increased commitment.…”
Section: Limitations and Future Research Avenuesmentioning
confidence: 99%
“…Although performance-based EI tests show a lower predictive effect on work-related criteria than self-report EI instruments, it is plausible that there were other relevant variables that we were unable to include in the proposed model and that would show a predictive role on occupational commitment (e.g., self-efficacy, [11]). Therefore, it would be valuable in future comprehensive works to test the joint contribution of personal resources (e.g., emotion regulation abilities, resilience, or self-efficacy beliefs) and contextual factors (e.g., professional support from colleagues or perceived autonomy support) to increased vigor and commitment [2,52,53]. Such an approach would beneficially advance knowledge in the fields of environmental research and public health as it might point out to the most relevant conditions and resources facilitating well-being among novice teachers [1,2].…”
Section: Limitations and Future Research Avenuesmentioning
confidence: 99%
“…It also is found that the social and personality competence of teachers must also be considered in teaching online. [15] State that teachers' socialemotional competence is considered important to master the social and emotional challenges inherent in their profession and to build positive teacherstudent relationships. The better the competence possessed by the teacher including social competence, the more positive impact it will have on students' competencies.…”
Section: Resultsmentioning
confidence: 99%